Assessing metarepresentational abilities in adolescence: an exploratory study on relationships between definitional competence and theory of mind - Cornaggia, Alessia; Bianco, Federica; Castelli, Ilaria; Belacchi, Carmen (Frontiers in Psychology, 2024)
Introduction Several developmental changes occur in adolescence, particularly in the metarepresentational domain, which allows and promotes adaptive sociality. We explored the possible relationships between theory of mind (ToM) and definitional competence, both metarepresentational, beyond age and gender effects. Methods To reach our goals, we involved 75 adolescents (age range 14–19 years, M = 15.7, and SD = 1.36). ToM was measured through “The Reading the Mind in the Eyes Test” (RMET), and definitional competence was assessed through a new instrument, namely, the “Co.De. Scale”. Attention was paid to check whether results were different when considering mental states vs. non-mental states of the scale and emotional words vs. non-emotional words. Results T-tests showed that older adolescents (third grade of high school) performed better than younger ones (first grade of high school) in both tasks. Only in the male group, there were no school grade differences in the ToM task. Regression analyses showed that RMET performance predicted the score of non-emotional mental states definitions and, even if marginally, of ToM word definitions. However, RMET was not a predictor of the general performance of the definitional task or emotion definitions. Discussion Connections with global adolescents’ development and possible educational implications are discussed.